The Key Factors in Increasing the Economic of the Coastal Village Community in Madura Island - Riniwati, Harsuko; Utami, Tiwi Nurjannati; Viantika, Risya; Galisong, Ridwan; Novia Putri Anjani (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
The economic condition of most coastal communities in Indonesia-including in Madura Island- is very vulnerable. This study aims to analyze the key factors for increasing the economy of community in the Madura Coastal Village. The Matrix of Direct Influences and Matrix of Indirect Influences (MICMAC) methods is used in this study. Respondents were experts in fisheries from the government, educational institutions, fishery business actors, and the community in Madura Coastal Village. The results show that the key factors for increasing the economy in the Madura Coastal Village are 1) modern technology, 2) ecotourism, 3) processing industry, 4) fishing business, 5) market guarantees, 6) promotion, 7) non-fishery business, 8) active role of government, 9) infrastructure. The government and academics need to provide education and train public about modern technology, take advantage of opportunities to increase income from ecotourism, processing fishery, and non-fishery businesses through promotion. The government is also expected to provide market guarantees and infrastructure facilities to support the economic sector of the coastal communities.